Insights from EU Policy Framework in Aligning Sustainable Finance for Sustainable Development in Africa and Asia - Liyanage, Shantha Indrajith H.; Netswera, Fulu Godfrey; Motsumi, Abel (International Journal of Energy Economics and Policy, 2020)
It is conspicuous that the mainstream financial system in the EU is transforming into a sustainable financial system by a supra/national policy and institutional framework for meeting the goals of SDGs and the targets of the Paris Agreement for climate change together with Nationally Determined Contribution. However, Botswana or Sri Lanka has no such framework. Hence, a need of the hour has arisen to evaluate the sustainable finance policies in Botswana, Sri Lanka, together with the EU seeking insights from the EU's policy framework. Since sustainable finance is not a well-grown branch of the conventional mainstream financial system, the nature of the knowledge is produced by social constructivism based on the grounded theory and the theory is inductively developed for achieving the purpose of the research. The study found, among other things, that incorporating existing policies into the multiple ministries and affiliated institutions together with the current industry-led policy initiatives to manage ESG risks are not adequate. Hence it is recommended various insights to be taken into consideration by the policymakers to formulate a national framework for mobilizing public and private capital to meet the goals of sustainability. Keywords: Sustainable Finance, Policy framework, Paris Climate Agreement, Sustainable Development Goals, Environmental, Social & Governance JEL Classifications: E65, F36, F38, L51 DOI: https://doi.org/10.32479/ijeep.9865